Civic Engagement in Local Multicultural Communities of Southern Russia - G. Volkov, Yuriy; V. Lubsky, Anatoly; V. Kovalyov, Vitaliy; Yu. Kolesnikova, Elena; A. Aslanov, Yakov (International Journal of Psychosocial Rehabilitation, 2020)
The article presents aspects of civil activity in the South of Russia in the context of formation of civil institutions in multicultural regional societies. The researchers note that the complex ethno-cultural structure of Southern Russia regional population has a significant impact on civil activity. The empirical basis of scientific study of civil activity is a set of empirical information sources, including the results of sociological research based on the methods of population questionnaire survey, focus groups and expert interviews. The authors conclude that civil activity in the South of Russia is initiated mainly from upstairs by state authorities or various public organizations. In local multicultural communities, there is also an increase in civil activity due to participation of people in civil protest actions organized from upstairs by representatives of opposition forces. On the other hand, there is also an increase in practice of civic activism in the framework of grass-roots civic initiatives aimed at organizing charitable actions to help people in difficult situations, and environmental actions related to environmental protection and formation of environmental culture. This research can be used for the universities, teachers and students. In this study the authors expanded their understanding of civic engagement in local communities in the South of Russia. The study reveals the reasons for civil passivity in local communities, which, according to the authors, lie in specifics of Russian mentality structure where ideas, values and attitudes of statist-paternalistic nature play a large role.